Plasma Reactors and Plasma Thrusters Modeling by Ar Complete Global Models - Chloe Berenguer; Konstantinos Katsonis (International Journal of Aerospace Engineering)
A complete global model for argon was developed and adapted to plasma reactor and plasma thruster modeling. It takes into consideration ground level and excited Ar and Ar+ species and the reactor and thruster form factors. The electronic temperature, the species densities, and the ionization percentage, depending mainly on the pressure and the absorbed power, have been obtained and commented for various physical conditions.